Age distribution of human papillomavirus infection and neutralizing antibodies in healthy Chinese women aged 18–45 years enrolled in a clinical trial. (August 2020) - Wei, L.-H.; Su, Y.-Y.; Hu, Y.-M.; Li, R.-C.; Chen, W.; Pan, Q.-J.; Zhang, X.; Zhao, F.-H.; Zhao, Y.-Q.; Li, Q.; Hong, Y.; Zhao, C.; et al.
Abstract: Objectives: Data from clinical trials of human papillomavirus (HPV) vaccines showed that women naïve (negative for both type-specific antibodies and DNA) to vaccine types would derive benefit from vaccination; therefore, an understanding of the proportion of naïve women in different age groups is important for developing HPV vaccination strategies. Methods: From November 2012 to April 2013, a total of 7372 healthy women aged 18– 45 years were recruited in five provinces in China. Cervical specimens and serum samples were collected for each woman at entry. Cervical specimens were first tested by the HPV DNA enzyme immunoassay method; if positive, the specimens were then tested by reverse hybridization line probe assay and HPV-16 and HPV-18 specific polymerase chain reactions. Neutralizing antibodies against HPV-16 or HPV-18 were tested with a pseudovirion-based neutralization assay. Results: The overall prevalence of high-risk HPV DNA was 14.8% (1088/7367, 95% CI 14.0–15.6), and the seroprevalence of neutralizing antibodies against HPV-16 and HPV-18 was 12.6% (925/7367) and 4.9% (364/7367), respectively. In younger women (18–26 years) and middle-aged women (27–45 years), 83.8% (3116/3719) and 81.4% (2968/3648) were naïve to both HPV-16 and HPV-18 (both neutralizing antibodies and DNA were negative), respectively. In addition, 98.5% (3664/3719) and 98.0% (3575/3648) of the younger or middle-aged women were naïve to at least one HPV type (HPV-16 or HPV-18). Discussion: This study revealed that the majority of Chinese women aged 18– 26 years and 27– 45 years were naïve to both HPV-16 and HPV-18 and would thus derive full benefit from bivalent HPV vaccination.